Continuities in times of change: Islamization of Human Knowledge amongst the AHAS KIRKHS’ academics during the Sejahtera Academic Framework period - Zamri, Zahid (2022)
Islamization of Human Knowledge (IoHK) has been the philosophical foundation of the International Islamic University Malaysia since its inception. However, the advent of the Sejahtera Academic Framework requires the revision of the University’s philosophy. The study attempts to look at how the proponents of Islamization of Human Knowledge, particularly amongst the academics of the AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, coped with the theoretical revisions that are happening at the University. Data are collected through intensive interviews with these academics and from documents related to them. Grounded theory is deployed as the research methodology. The study focuses on the academic activities and the revisionist discourse conducted by these IoHK proponents as well as on matters related to the privacy of thoughts of these academic-intellectuals. The study found that the IoHK agenda continues to flourish albeit in/through new “forms” of academic exercises and activities as carried out by the IoHK espousers during the revision period.